ENTEROPARASITOSIS IN PUBLIC SCHOOLS IN BAHIA: PARASITOLOGY LEARNING - Suarez-Fontes, Ana Márcia; Suarez Fontes, Sheila; Vannier-Santos, Marcos Andre (Revista de Patologia Tropical / Journal of Tropical Pathology, 2017)
Parasitic diseases hamper progress in underdeveloped nations, compromising child physical and cognitive development. In order to control intestinal parasites, the popularization of science may enable prophylactic measures. Questionnaires were used to assess the students’ knowledge, attitudes and practices. Health fairs were held as an educational tool and subsequently questionnaires on parasitic diseases and prevention were administered. Stool examinations were performed and infected students were treated. Prevalence of Entamoeba histolytica/ dispar, Ascaris lumbricoides, Trichuris trichiura was 7.1%, 5% and 3.5% respectively in the Anísio Teixeira Institute students and 7.2%, 8%, 3.6% in the Raymundo Matta School students in a suburb. The students at both schools displayed limited knowledge on parasitic disease prevention. The school participation in the prophylaxis of parasitic diseases, was not acknowledged by the students. Reviewing curricula is required, addressing themes related to health, possibly establishing partnerships with health services, universities and/or research centers with the effective involvement of the community performing articulated actions in different health districts, so that education will lead to community empowerment in regard to quotidian issues and improving public health conditions.